Inflammatory Periodontal Diseases and its Complex Methods Treatment - Xojimurodov Burxon Ravshanovich (Open Academia, 2023)
Periodontal disease is currently one of the most common diseases in dental practice, affecting patients of all ages. The structural and functional status of the periodontium, as well as other mucous membranes, depends on the activity of the hormonal background in the body. As practice shows, the bacterial flora is the underlying cause of periodontal disease in only 20% of cases, and microorganisms are primarily secondary aggravating factors, not causative factors. If bacteria were the cause of periodontal disease, cleaning solutions and disinfectants would have already solved the problem by the first or second day, but unfortunately this is not the case in practice. It is time to analyze the composition of the microflora of the plaque and determine which microflora should be directed to medical treatment, as in gingivitis and periodontitis. The main microorganism that must already be fought in gingivitis is P. gingivalis, which has many pathogenic properties. Embedded in epithelial cells and tooth ligaments, it produces leukotoxins that destroy neutrophils, enzymes that degrade the protein matrix, and gram-negative bacteria produce metabolites that lyses bone. Speaking of microcirculatory disturbances, activated by inflammation, microvessels begin to grow actively and continuously, forming many immature inflammatory vessels, which lack a central elastic wall and are complex and fragile (bleeding gums are seen in the clinic). The leading links of blood flow increase and outflow (venous network) remains unchanged, resulting in venous stagnation, accumulation of metabolic toxins and extracellular fluid, tissue edema, and impaired cellular communication and interaction. This process enters a chronic phase and is self-sustaining, so that no new periodontal ligament can be formed.